Recent Recovery of the World’s Rarest Primate Is Not Directly Linked to Increasing Habitat Quality - Zou, Yike; Turvey, Samuel T.; Cui, Jie; Zhang, Hui; Gong, Wenfeng (Frontiers in Ecology and Evolution, 2022)
Due to habitat loss and hunting, the Hainan gibbon (Nomascus hainanus), the world’s rarest primate, was reduced to only two social groups and seven known individuals in 1978. Following the establishment of Bawangling National Natural Reserve (BNNR), gibbon forest habitat increased within this landscape from 56 km2 in 1980 to 300 km2, and the species had increased to five groups and 35 individuals by 2021. It is important to assess whether the large increase in habitat area was responsible for gibbon population increase, or whether gibbon recovery was associated with other factors. Here we use a 21-year longitudinal dataset of Hainan gibbon population change and habitat change, combined with vegetation survey plot data for 2021, to establish an accurate distribution baseline for natural tropical broadleaf forest across the BNNR landscape from 400 to 1300 m (the elevational range of gibbons at BNNR) and within the home range for each of the five Hainan gibbon social groups. We then utilized Landsat time-series images and analysis to compute non-linear causal relationships between forest dynamics and gibbon population growth from 2000 to 2021, both across BNNR and within each gibbon group home range. Metrics of forest dynamics include change in total forest area and forest fragmentation, and metrics of gibbon population dynamics include variation in total number of individuals for the entire population and within each social group, and variation in total number of groups. Our results demonstrate that overall gibbon population growth shows a positive relationship with improved habitat quality, with a one-year time lag of population response. However, changes in numbers of individuals within social groups do not show a similar relationship with improving habitat quality, suggesting that increasing forest cover and connectivity within the BNNR landscape are not direct determinants of Hainan gibbon recovery and that other environmental and/or anthropogenic factors are likely to be involved.